Adaptive responses of the neuromuscular system to training - Gollhofer, A. (New Studies in Athletics, 2007)
Strength training leads to functional adaptations of the musculo-skeletal system as well as to the neuromuscular system. The properties of muscular activation can be changed to a large extent depending on the type of strength training. For athletic performance the power of muscular action is often much more important than the maximum in force capacity. Thus, training needs to recognize this aspect appropriately in order to find best training parameters to improve power. Sensormotor training has proved to be highly effective, not only with respect to clear and considerable improvements in muscle power, but also with respect to enhanced postural control. Especially for team sports the improvement in postural control is very efficient in the reduction of injuries to the lower extremities. In the present paper focus is given on the physiological pathways to explain the functional adaptations of power strength training, in order to give coaches and athletes the explanations why sensormotor training can be beneficial for enhanced rate of force development capabilities.